factor by grouping 7a^3+7ab^2+4a^2b+4b^3

7a^3+7ab^2+4a^2b+4b^3 =7a(a^2+b^2)+4b(a^2+b^2) =(7a+4b)(a^2+b^2)

Question

Asked 2/19/2013 9:30:01 AM

Updated 5/9/2015 10:56:01 PM

1 Answer/Comment

Rating

3

7a^3+7ab^2+4a^2b+4b^3

=7a(a^2+b^2)+4b(a^2+b^2)

=(7a+4b)(a^2+b^2)

=7a(a^2+b^2)+4b(a^2+b^2)

=(7a+4b)(a^2+b^2)

Added 5/9/2015 10:56:01 PM

This answer has been confirmed as correct and helpful.

Confirmed by Andrew. [5/10/2015 9:04:28 AM]

27,077,167

questions answered

There are no comments.